Professional Skepticism in Moderating the Relationship between Auditors’ Knowledge, Obedience Pressure, and Auditors’ Experience on Audit Judgment - sumartono sumartono (Jurnal ASET (Akuntansi Riset), 2022)
This study analyzed the role of professional skepticism in moderating the relationship between auditors’ knowledge, obedience pressure, and auditors’ experience on audit judgment. The population in this study included all government internal auditors at BPKP Papua Province Representatives. Purposive sampling technique was employed to select 79 samples based on these following criteria: government internal auditors who possessed Functional Auditor certification, and government internal auditors who have performed auditing. Data were collected using questionnaire containing 29 statement items and were measured using a Likert scale. Moderated regression analysis (MRA) method was performed to analyze the data. The results showed that Auditors’ knowledge, Obedience Pressure, and Auditors’ experience had a significant positive influences on Audit Judgment, and Professional Skepticism moderated the influence of Auditors’ knowledge, Obedience Pressure, Auditors’ experience on Audit Judgment. Therefore, the improvement of internal auditors’ professional responsibility in the form of Audit Judgment should take into account the role of Professional Skepticism. This study only used closed statements in the questionnaires. Thus, future researchers are recommended to use the combination of the of both open-ended and closed ended statements